The History of Animals in the Present Moment: Rumination 2.0 - Fudge, Erica (Humanimalia, 2022)
This ‘Rumination’ updates my original ‘Rumination’ on animal history from 2006 and looks back over the past fifteen years at the ways that the field of animal history has developed. It turns, in the conclusion, to think about the impact that discussions about the Anthropocene have had on historiographical discussions.